Motivasi Kebertahanan Pelaku Kegiatan Pertanian di Perkotaan Studi Kasus Kecamatan Gunungpati dan Kecamatan Mijen, Kota Semarang - Tyas Mila Zuliastuti; Bambang Hari Wibisono (REKA RUANG, 2022)
Land use conversion from agricultural to non-agricultural use is unavoidable in urban settings. Land use competition which causes land value increments becomes the main reason for land use conversion. However, few urban dwellers are still willing to utilize their land for agricultural use. Therefore this research is conducted to investigate the motivation behind the willingness of the urban farmer to maintain agricultural activity in an urbanized area, with a case study in Gunungpati and Mijen District in Semarang, Central Java. This research utilizes a case method approach with a holistic multiple case design model to reveal the informant's motivation to maintain agricultural activity in the case study area. This research identified several motivational factors that underlie the willingness of the informants to maintain agricultural activity in the case study area, which are the motivation to fulfill basic, economic, social, security, appreciation, self-actualization, and natural preservation needs.